Marginalized Wisdom: Empowering Customary Law in Family Conflict Resolution - M Taufan Badollahi; Sapruddin Saprudin; Sitti Nurkhaerah; Arief Budiono; Absori Absori; Muhammad Amin Hanafi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to construct the form of customary law empowerment as a means of overcoming family conflict. The research design used is empirical legal research with a qualitative-naturalistic approach. The research was conducted in Palu City, especially in Birobuli Utara Village. The data for this study came from field observations and interviews with traditional leaders. The results of the study indicate that customary law empowerment as a means of overcoming family conflict is constructed in the form of implementing alternative dispute resolution, a method of resolving disputes outside the court with mediation and negotiation techniques. Customary law empowerment as a means of overcoming family conflict should continue to be strengthened from various aspects so that it can be more optimal in carrying out its function as an alternative dispute resolution institution, considering that this institution has been proven to be able to resolve family disputes simply, quickly, and at low cost (speedy administration of justice), while maintaining community harmony. Otherwise, this very valuable social capital will only become wisdom that is increasingly being marginalized.